Conflict of Customs and Islamic Law in Tatangkok Marriage Practices in IV Koto Barat Kinali, West Pasaman Regency: Konflik Adat Dan Hukum Islam Dalam Praktik Nikah Tatangkok Di IV Koto Barat Kinali Kabupaten Pasaman Barat - Rizky Firman Nugraha; Muhammad Royhan; Mutia Hafizah (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study examines the practice of nikah tatangkok in Nagari IV Koto Barat Kinali, Kinali District, Pasaman Barat Regency, a form of marriage imposed as a customary sanction on couples caught engaging in immoral acts. This practice generates a normative dilemma because it potentially conflicts with Islamic legal principles, particularly the requirement of consent (riḍā) as a condition for a valid marriage contract. The study aims to identify the factors that lead to the occurrence of nikah tatangkok, describe its implementation process, and analyze its legal validity from the perspective of Islamic law. The research employs a qualitative approach with a case study method, conducted throughout 2023. Primary data were obtained through in-depth interviews with sixteen key informans, including the hamlet head, youth leader, traditional leaders, community figures, parents of the involved parties, and couples who had undergone the practice. These findings are strengthened by documentation of nikah tatangkok cases from 2020 to 2023, which recorded a total of five couples subjected to this process. Data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The findings reveal that nikah tatangkok is driven by three main factors: violations of moral norms perceived as tarnishing the honor of the nagari, the strong culture of social surveillance, and the community’s belief that repressive action is necessary to prevent greater harm. The process consists of several stages, including suspicion, capture, interrogation, customary deliberation, and the execution of the marriage contract. From an Islamic legal perspective, the practice does not fully align with the principle of voluntary consent, although some people consider it an effort to prevent broader social impact, this is in accordance with the principle of sadd al-dzari’ah. The study highlights the normative conflict between Minangkabau customary law and Islamic law and underscores the importance of legal education to ensure marriage practices are more just and consistent with Islamic principles.